Proceedings of the First International Conference on Information and Computation Economies 1998
DOI: 10.1145/288994.289022
|View full text |Cite
|
Sign up to set email alerts
|

Quality of service provision in noncooperative networks

Abstract: This paper studies the quality of service (QoS) provision problem in noncooperative networks where applications or users are selfish and routers implement generalized processor sharing (GPS)-based packet scheduling. First, we formulate a model of QoS provision in noncõ perative networks where users are given the freedom to choose both the service classes and traffic volume allocated, and heterogeneousQoS preferences are captured by individual utility functions. We present a comprehensive analysis of the noncoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…This implies that multi-media applications|a tra c source with voluminous data rate requirements which promotes a structural environment conducive t o n e t work tra c self-similarity|are also the tra c sources that su er most from their sensitive quality of service (QoS) requirements unless resource reservations or strati cation of best-e ort services is employed. 20 Increasing link bandwidth, given a xed large bu er capacity, has the e ect of decreasing queueing delay m uch more drastically under highly self-similar tra c conditions than when tra c is less self-similar. This suggests that high-bandwidth communication links be employed to alleviate the exponential trade-o relationship between queueing delay and packet loss/throughput for supporting QoS-sensitive tra c. The e ect of bandwidth on queueing delay i s m uch less pronounced when bu er capacity i s small.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that multi-media applications|a tra c source with voluminous data rate requirements which promotes a structural environment conducive t o n e t work tra c self-similarity|are also the tra c sources that su er most from their sensitive quality of service (QoS) requirements unless resource reservations or strati cation of best-e ort services is employed. 20 Increasing link bandwidth, given a xed large bu er capacity, has the e ect of decreasing queueing delay m uch more drastically under highly self-similar tra c conditions than when tra c is less self-similar. This suggests that high-bandwidth communication links be employed to alleviate the exponential trade-o relationship between queueing delay and packet loss/throughput for supporting QoS-sensitive tra c. The e ect of bandwidth on queueing delay i s m uch less pronounced when bu er capacity i s small.…”
Section: Introductionmentioning
confidence: 99%
“…Several works have also studied the [33], [39], [40] priority queueing systems (a la Diffserv) under game-theoretic frameworks. So for example, Marback [33] analyzes a priority queueing scheme where packets get charged based on their priority, and selfish users compete for bandwidth.…”
Section: Related Workmentioning
confidence: 99%
“…A fundamental distinction in this case is that T&C enables different valuations for different classes of traffic, and uses these valuations to leverage the trading system. Park et al [39] consider a QoS class assignment game where users share a single Generalized Processor Sharing (GPS) queue and they can assign the class for the traffic. Users do so, to meet the QoS requirements of their application at the minimum possible costs (as higher priority also means higher cost).…”
Section: Related Workmentioning
confidence: 99%
“…This assumption was challenged by [22], where it was shown that for a natural class of games their realistic utility functions-based on a commonly used network model-are not quasiconcave and result in natural QoS provision games that may not have Nash equilibria.…”
Section: Article In Pressmentioning
confidence: 99%
“…One approach by the networking [1,6,5,12,27,26,21] research community over the past several years is to use a microeconomic model: treat the network as a market and its users and providers as players of a noncooperative game [9,6,5,22]. A number of related, fundamental issues have been isolated-in algorithmic mechanism design, computational aspects of game theory, and complexity of distributed computing and communication-that are of interest to theoreticians [2,16,17,19,20,25] and potentially have other applications as well.…”
Section: Introductionmentioning
confidence: 99%